Clinical evaluation and management of endometriosis: 2024 guideline for Korean patients from the Korean Society of Endometriosis - Hyun Joo Lee; Sang-Hee Yoon; Jae Hoon Lee; Youn-Jee Chung; So Yun Park; Sung Woo Kim; Yeon Hee Hong; Sung Eun Kim; Youjin Kim; Sungwook Chun; Yong Jin Na (Obstetrics & Gynecology Science)
Endometriosis, a prevalent but debilitating condition affecting women, poses significant challenges in diagnosis and management. The current 2024 guideline, developed by the Korean Society of Endometriosis (KSE), builds upon the 2018 KSE guideline. This guideline aims to provide customized recommendations tailored to Korea’s unique clinical aspects and medical environment, and addresses key areas such as diagnosis, medical and surgical management, considerations for special populations, and its complex relationship with cancer.